Relationship Between Soft Skills And Teaching Competency Of Higher Secondary Teachers (Journal of Namibian Studies : History Politics Culture, 2022)
In this study, an attempt has been made to study the relationship between soft skills and teaching competency among higher secondary teachers. The Soft Skills Scale(SCS) and Teaching Competency Scale (TCS) are constructed and validated by the investigator (2023), were used to collect the data from a sample of 605 higher secondary teachers in Nilgiri District, Tamil               aadu in India. The descriptive survey method has been followed and simple random sampling technique was used in administration of the research tools. The result indicated that the there is significant and positive relationship between sot skills and teaching competency of higher secondary teachers, there is a significant contribution of teaching competency and dependent variable on the teaching competency of higher secondary teachers i.e. 54.8% of the total variance in sot skills is attributed by teaching competency.